SEABIRDS IN THE BANDA SEA IN FEBRUARY/MARCH 1985 - Cadee, G. C. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1989)
Quantitative seabird data were collected in February/March 1985 in the Banda Sea. Comparison with similar data for August 1984 indicated no monsoonal influence on seabrid abundance; the median for both periods falls within the 1-5 birds per hour class.The area around the breeding island Manuk was relatively rich in both periods. Birds breeding here are